Profile of Nasopharyngeal Cancer Patients who Underwent Radiotherapy in Dr. Hasan Sadikin General Hospital Bandung - Indira Meidina Nafisa; Marhendra Satria Utama; Mas Adi Sunardi; Antony Abel Adibrata (Indonesian Journal of Cancer, 2022)
Background: Nasopharyngeal cancer (NPC) is a malignant epithelial tumor located in the nasopharynx and is the most common head and neck malignancy. This study aimed to find and describe the profile of NPC patients who undergo radiotherapy at Dr. Hasan Sadikin General Hospital, Bandung.Methods: This study was a descriptive study conducted at the Department of Radiology of Dr. Hasan Sadikin General Hospital, Bandung. This study employed a total sampling method and was done by observing patients’ status/medical records from January 1, 2018, to December 31, 2019, which was registered based on the Hospital-Based Cancer Registry (HBCR). The inclusion criteria were all patients diagnosed with NPC and undergone radiotherapy.Results: There were 274 records (19.74%) included as NPC from 1,388 records. This cancer was more frequent in men (70.4%), in the age group of 45–54 years (35.0%), non-active smokers (58.8%), entrepreneurs (23.0%), and those who came from West Priangan (36.1%). The most common chief complaint was an enlargement of neck lymph nodes (55.1%) at stage IVB (42.8%). Histopathological findings were dominated by undifferentiated squamous cell carcinoma (WHO III) (74.4%). Most of the patients were treated with chemoradiation (64.3%).Conclusions: NPC could happen to anyone with different background. This study found it was more frequent in men than women (2.3:1), in the fourth and fifth decade of life, in entrepreneurs followed by housewives, and even in non-active smokers. It also could happen in children to the elderly. Most patients came with an enlargement of neck lymph nodes as their chief complaint in the advanced stage and need chemoradiation as their treatment.